Literacy Cloud Media for Improving Reading Aloud Skills in Elementary School: Media Literasi Awan untuk Meningkatkan Keterampilan Membaca dengan Suara Nyaring di Sekolah Dasar - Nisa, Ayu Khoirun; Nuroh, Ermawati Zulikhatin (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Reading aloud is a fundamental language skill that supports students’ fluency, comprehension, and confidence in communication. Specific background: Despite its importance, many elementary students still face challenges in practicing reading aloud, and limited digital resources have been fully integrated into learning. Knowledge gap: Previous studies have explored digital media for literacy, yet there remains little evidence regarding the role of Literacy Cloud in strengthening reading aloud skills among younger learners. Aims: This study investigates the use of Literacy Cloud as a digital learning medium to improve reading aloud skills among third-grade students at SDN Sentul. Results: A quantitative approach with paired sample t-test analysis revealed a significant improvement in students’ reading aloud performance, with sig. (1-tailed) = 0.000 < 0.05 and an eta squared value of 0.93, indicating a large effect. Novelty: The integration of Literacy Cloud in reading instruction provides a digital innovation that directly addresses fluency practice in elementary education. Implications: The findings highlight the importance of adopting digital media in classrooms to foster students’ literacy development, offering practical insights for teachers, policymakers, and curriculum designers in enhancing reading pedagogy through technology. Highlights: Literacy Cloud significantly improved students’ reading aloud skills Eta squared value indicated a large contribution of the media Digital media integration supports literacy development in primary education Keywords:Literacy Cloud, Reading Aloud, Elementary School, Digital Media, Literacy Skills